A Numerical Study on Cross Diffusion Cattaneo-Christov Impacts of MHD Micropolar Fluid Across a Paraboloid - K, Kalyani; N, Seshagiri Rao; M.V.V.N.L., Sudha Rani (Iraqi Journal of Science, 2021)
Analyzing the impacts of Cattaneo-Christov flux, bioconvective Raleigh number and cross diffusion effects in electrically conducting micropolar fluid through a paraboloid revolution is assessed in this work. Non-dimensional equations are solved numerically using shooting technique with an aid of Matlab software. The impact of various parameters on velocity, temperature and concentration are discussed in detail and presented graphically. Harman number and micro rotation parameters are found and have an increasing influence on shear stress. The vertical velocity increases at free stream and the horizontal velocity increases near the surface when Grb increases, which follows the opposite trend for accumulation of Rb. The numerical results are compared with the available data indicating good agreement in a limiting case.